2004
DOI: 10.1023/b:emas.0000029893.27432.1c
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Plant Diversity at Landscape Level: A Methodological Approach Applied to Three Spanish Rural Areas

Abstract: Approaches linking biodiversity assessment with landscape structure are necessary in the framework of sustainable rural development. The present paper describes a methodology to estimate plant diversity involving landscape structure as a proportional weight associated with different plant communities found in the landscape mosaic. The area occupied by a plant community, its patch number or its spatial distribution of patches are variables that could be expressed in gamma plant diversity of a territory. The met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 6 publications
2
17
0
Order By: Relevance
“…All in all, Duelli (1997, 88) and many other authors (e.g., Bailey et al, 2007;Ortega et al, 2004) hold that the evaluation of patterns of the landscape mosaic can serve as a substitute for the recording of regional biological diversity, as a form of knowledge-based assessment. In general, broad environmental diversity leads to high species diversity (Ricotta et al, 2003, 373).…”
Section: Results On Linkages Between Landscape Structure and Speciesmentioning
confidence: 99%
“…All in all, Duelli (1997, 88) and many other authors (e.g., Bailey et al, 2007;Ortega et al, 2004) hold that the evaluation of patterns of the landscape mosaic can serve as a substitute for the recording of regional biological diversity, as a form of knowledge-based assessment. In general, broad environmental diversity leads to high species diversity (Ricotta et al, 2003, 373).…”
Section: Results On Linkages Between Landscape Structure and Speciesmentioning
confidence: 99%
“…A 1,000 m 2 (50 m × 20 m) rectangular plot was established following Whittaker's multi-scale plot design, modified by Stohlgren et al, (1995) and Ortega et al (2004), for sampling the presence and abundance of vascular plant species in each mesohabitat. In the core of each mesohabitat, the plot is located at least 100 m far from the nearest edge, following the steepest slope in order to record a major environmental variability.…”
Section: Data Collectionmentioning
confidence: 99%
“…Late spring (MayJune) was considered to be the optimal phenological season (peak phenology sensu Stohlgren, 2007) for identifying the highest number of plant species. This methodology is useful for the comparison of plant diversity richness at different scales (see Stohlgren et al, 1997;Wagner et al, 2000;Ortega et al, 2004). The use of 0.1 ha plots reduces the variability of total species recorded as has been reported by Aronson and Shmida (1992) with five year series in Mediterranean environments of Israel, in order to compare samples from different years.…”
Section: Data Collectionmentioning
confidence: 99%
“…The studies done so far in terms of the richness and diversity of plant species, varies according to the land use type and relationship between soil properties and topography has generally examined the of the study (Janssens et al, 1998;Pärtel, 2002;Palmer et al, 2003;Ortega et al, 2004;Bohner, 2005). Ortega et al (2004) investigated plant diversity using Shannon-Wiener and Simpson diversity indexes in the different land use type by land scale in three different rural areas, have identified more plant species in grassland compared to other areas.…”
Section: Introductionmentioning
confidence: 99%
“…Ortega et al (2004) investigated plant diversity using Shannon-Wiener and Simpson diversity indexes in the different land use type by land scale in three different rural areas, have identified more plant species in grassland compared to other areas. In addition, reported that combined with land use characteristics and plant diversity shed light on the feature of land in the interpretation of ecological studies.…”
Section: Introductionmentioning
confidence: 99%